Target-triggered cascade recycling amplification for label-free detection of microRNA and molecular logic operations. Issue 2 (3rd November 2015) - Bi, Sai; Ye, Jiayan; Dong, Ying; Li, Haoting; Cao, Wei
Abstract : A cascade recycling amplification (CRA) that implements cascade logic circuits with feedback amplification function is developed for label-free chemiluminescence detection of microRNA-122 with an ultrahigh sensitivity of 0.82 fM and excellent specificity, which is applied to construct a series of molecular-scale two-input logic gates by using microRNAs as inputs and CRA products as outputs. Abstract : A cascade recycling amplification (CRA) that implements cascade logic circuits with feedback amplification function is developed for label-free chemiluminescence detection of microRNA-122 with an ultrahigh sensitivity of 0.82 fM and excellent specificity, which is applied to construct a series of molecular-scale two-input logic gates by using microRNAs as inputs and CRA products as outputs.